Mycophenolate mofetil for primary focal segmental glomerulosclerosis: systematic review. (July 2013) - Lau, Emily W.Y.; Ma, Polly H.X.; Wu, Xinyin; Chung, Vincent C.H.; Wong, Samuel Y.S.
Abstract Background: Current treatments for primary focal segmental glomerulosclerosis (FSGS), including corticosteroids and cyclosporine, are not satisfactory for all patients and may induce significant side effects. Antidotal benefits of mycophenolate mofetil (MMF) as an add-on to these immunosuppressive therapies have been reported. This review aims to systematically summarize the efficacy and safety of MMF as a treatment for primary FSGS. Method: Controlled and uncontrolled clinical trials evaluating the use of MMF in primary FSGS patients were identified from nine electronic databases and four clinical trial registries. Kidney failure was selected as the primary outcome. Results: Three randomized controlled trials (RCT) and 18 uncontrolled pre-post studies were included. Results from RCTs revealed that MMF is no more effective than cyclosporine or cyclophosphamide for promoting kidney function preservation when corticosteroid is used as baseline treatment. One underpowered RCT reported that MMF provides no extra benefit on top of prednisolone, but the result is unlikely to be reliable. Amongst the small, uncontrolled pre-post studies, three of them used MMF as monotherapy, two of which reported successful prevention of kidney failure in all patients. The remaining 15 uncontrolled studies used MMF as add-on therapy and 11 reported kidney failure as an outcome. Amongst them, eight reported no patients developed kidney failure. MMF was generally well tolerated with mild adverse effects, including abdominal discomfort, diarrhea and infections. Conclusions: MMF tended to show beneficial effects in uncontrolled studies which recruited patients with resistance to routine treatments, but such favorable results have only been reported in small, uncontrolled trials. No RCT results suggested that MMF was a good alternative to cyclosporine or cyclophosphamide. The role of MMF as an add-on to current therapies, or as monotherapy, should further be evaluated.